Palliative care clinical nurse specialists leading enhanced supportive care in hepatopancreatobiliary cancer. (2nd March 2023) - Benson, Sinead; Wong, Helen; Olsson-Brown, Anna; Coyle, Seamus; Monnery, Daniel
Abstract : Background: Integration of care between palliative care and oncology can improve patient outcomes and is increasingly recommended. Enhanced supportive care (ESC), led and delivered by palliative care clinical nurse specialists, is a potential model to achieve this but evidence about it is lacking. Aim: This research aimed to evaluate a nurse-led integrated ESC model within hepatopancreatobiliary cancer care. Method: Some 101 patients with hepatopancreatobiliary cancer were supported by integrated ESC delivered in a co-located clinic. Data on symptoms and quality of life were collected prospectively. Survival data and chemotherapy use were retrospectively analysed following minimum follow-up, using a matched control technique. Results: Patients receiving ESC exhibited less severe symptoms and better mood over time. They also had less aggressive treatment towards the end of life, receiving 31% less chemotherapy than controls with comparable survival. Conclusion: An integrated, nurse-led ESC model can be effective in improving outcomes for patients with hepatopancreatobiliary cancer.